Peran Sekolah untuk Pemahaman Orangtua terhadap Nutrisi Anak sebagai Optimalisasi Motorik Disabilitas Intelektual di SLBN 1 Buleleng: Penelitian - Vio Firliana; Erick Burhaein (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze the role of schools in improving parents’ understanding of nutrition for elementary school-aged children as a means of optimizing the motor skills of students with intellectual disabilities at SLBN 1 Buleleng, Bali. The background of this study is since the implementation of nutrition education programs for parents at special education schools remains very limited they are held only once a year, and the materials do not cover adequate nutritional aspects. Meanwhile, the Nutritious Meals Program (PMB), which has been implemented at the school, has not been able to ensure the sustainability of its application in the home environment. This study employs a qualitative approach using a case study strategy. Data were collected through unstructured in-depth interviews, non-participatory observation, and document analysis. Information sources included the school principal, elementary school classroom teachers, Physical Education, Sports, and Health (PJOK) teachers, and parents of students with intellectual disabilities. Data validity was ensured through triangulation of sources and techniques. The results revealed that schools have great potential as mediators of nutrition education through four key dimensions: collaboration between schools and parents; the roles of teachers and school leaders; school policy concepts; and the influence of parental understanding on the optimization of children’s motor skills. The active involvement of PE teachers and school principals in educating parents was found to be associated with improvements in students’ motor skills. Based on these findings, this study recommends that nutrition education programs for parents be scheduled on a regular basis and designed to be inclusive as an integral part of special education policies.